Research Study Literature Review: Exploring Types of Smash Training Methods in Volleyball - April Andi Budianto; Leni Apriani (Kinestetik : Jurnal Ilmiah Pendidikan Jasmani, 2024)
The purpose of this study was to show that both training programs have a significant effect on performance in various aspects of volleyball, especially smashing, as well as muscle fitness and arm power, all of which contribute to improving volleyball technical abilities such as smashing, passing, and serving. The instrument used was the traditional literature review method . Based on ten articles in the form of research journals that have been analyzed by the author related to the title of the writing, namely Training Methods in Volleyball Sports, the approach innovative For increase technique and strength smash hit with use obstacle or tool help that is not conventional . This method aims to improve Power jumping , timing , accuracy , and creativity player in perform a deadly smash .